Wajah Jepang pada Era Heisei - Maharani Patria Ratna (Diponegoro University, 2019)
The Heisei era had changed to the Reiwa era in 2019. All the Japanese people entered a new phase of the Japanese imperial era. Emperor Akihito wanted to abdicate for health reasons, so the throne was replaced by emperor Naruhito. This study aims to look back at any significant events that occurred in the Heisei era. The method used is this research is a qualitative descriptive study. Data collected by the literature method through several articles about the Heisi era. The results of this study indicates that overall it can be said that peace has been achieved in Japan. The Heisei Era is an era filled with economic turmoil and disasters in Japan. In addition, the Heisei era also still leaves a heavy task for the Reiwa era, that is economic improvement after the economic bubble to revive the Japanese economy as before. Heisei era is indeed full of challenges for Japan, but international confidence in Japan is very high. By advancing its technological progress, Japan managed to become the organizer of the winter olympics in 1998 and the world cup in 2002.